Value in omni-channel retailing : Retailer and consumer perspectives in the grocery-retailing industry - Paunonen, Eveliina (My University, 2019)
New digital channels, such as grocery e-commerce and in-store technologies have offered an intriguing opportunity for traditional grocery retailers to engage their consumers. Even if omni-channel integration has been acknowledged as a key priority by many retailers, few previous studies have investigated the value of emerging channels and their integration in the context of grocery industry. This study aimed to address this research gap by investigating the value in grocery omni-channel retailing. The purpose of this study was to investigate the value of grocery omni-channel retailing from retailers’ and consumers’ perspectives. Multi-method qualitative design, combining six individual interviews with the retailers and two focus group discussions with the consumers was adopted. Research gave useful insights into the topic of the grocery omni-channel value. Findings suggest that grocery omni-channel value consists of seamless channel integration, as well as each grocery channel’s value, which derives from advantages and disadvantages related to the channel usage or deployment. The empirical analysis also brought up new advantages and disadvantages associated with the three main grocery channels; physical store, grocery e-commerce and mobile channel. From the retailers’ perspective, new advantages included increased service value associated with the in-store technologies, increase in one-off purchases and increased consumer satisfaction related to the e-commerce channel, as well as competitive advantages of mobile channel. The novel disadvantages consisted of loss of impulse purchases in grocery e-commerce channel as well as technical challenges and intrusiveness of multi-store mobile marketing associated with the mobile channel. From the consumers’ perspective, new perceived disadvantages included loss of control, problems with adaptation and limitations in available service times related to the e-commerce channel, as well as irrelevant offers associated with the mobile channel. Based on the findings of this study, many suggestions for the future research can be suggested. The managerial implications of this thesis may also be beneficial for the grocery retailers to further develop their omni-channel strategies and channel management.
Keywords: Omni-channel integration, omni-channel value, grocery e-commerce